2012
DOI: 10.1096/fj.11-201111
|View full text |Cite
|
Sign up to set email alerts
|

The novel chromogranin A‐derived serpinin and pyroglutaminated serpinin peptides are positive cardiac β‐adrenergic‐like inotropes

Abstract: Three forms of serpinin peptides, serpinin (Ala26Leu), pyroglutaminated (pGlu)-serpinin (pGlu23Leu), and serpinin-Arg-Arg-Gly (Ala29Gly), are derived from cleavage at pairs of basic residues in the highly conserved C terminus of chromogranin A (CgA). Serpinin induces PN-1 expression in neuroendocrine cells to up-regulate granule biogenesis via a cAMP-protein kinase A-Sp1 pathway, while pGlu-serpinin inhibits cell death. The aim of this study was to test the hypothesis that serpinin peptides are produced in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
1
43
0
1
Order By: Relevance
“…The results on the Chr-induced modulation of the cardiac performance extend the knowledge on the regulatory influence elicited by circulating CGA and its fragments (VS-1, CST and serpinin) on the mammalian cardiocirculatory system [37,38]. Nothing is known on how these actions, as well as the proteolytic events which generate CGA fragments, are spatiotemporally coordinated.…”
Section: Chr As a Cardioinhibitory Peptidesupporting
confidence: 63%
See 2 more Smart Citations
“…The results on the Chr-induced modulation of the cardiac performance extend the knowledge on the regulatory influence elicited by circulating CGA and its fragments (VS-1, CST and serpinin) on the mammalian cardiocirculatory system [37,38]. Nothing is known on how these actions, as well as the proteolytic events which generate CGA fragments, are spatiotemporally coordinated.…”
Section: Chr As a Cardioinhibitory Peptidesupporting
confidence: 63%
“…They are generated by proteolytic cleavage not only in secretory vesicles of chromaffin cells, the main site for CgA synthesis and release, but also in extramedullary sites, including the heart [13,28]. CgA-derived peptides include the N-terminal vasostatin-1 (CgA1-76; VS-1), catestatin (CgA352-372; CTS), and the C-terminal serpinin (Serp) [7,5,3,38]. All of them elicit direct effects on the rat heart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pozitív inotrop és lusitrop effektus jelentősen javítja a mechanikus kardiális teljesítményt; növekszik a szisztolés kamrai volumen, rövidül a diasztolés idő, továbbá tachycardiatendencia érvényesül és tágulnak az arteria coronariák. Ál-latkísérletben mutatkozik meg az intracardialis autokrin, parakrin hatásbeli út (ChrgrA-proteolysis, serpininkép-ződés, szívizomhatás, kardiális teljesítmény növekedése) [41][42][43][44]. Az eredmény szinte teljesen ellentétes a katesztatin-és vazosztatinhatásokkal.…”
Section: A Cardiovascularis Rendszer éS a Chrgr-okunclassified
“…Remarkably, also the CgA fragments can work as cardio-regulatory hormones, in certain cases with opposite functions. While, full-length CgA, vasostatin-1 and catestatin depress myocardial contractility and relaxation, counteract the b-adrenergic-induced positive inotropism, and modulate coronary tone (via a nitric oxidedependent mechanism) [16], a fragment corresponding to the C-terminal region CgA 411-436 , called serpinin, enhances myocardial contractility and relaxation (via a b-adrenergic-cAMP-PKA and nitric oxide-independent pathway) [16,[34][35][36][37]. Analysis of the effluents from ex vivo perfused rat hearts showed that exogenous CgA was not cleaved by the heart, suggesting that the circulating, full-length protein can directly induce myocardial effects [16].…”
Section: Cga and The Endothelial Barrier Functionmentioning
confidence: 99%